Analisis Yuridis Peraturan Gubernur Riau Nomor 14 Tahun 2021 Tentang Penerimaan Peserta Didik Baru pada Jenjang Sekolah Menegah Atas Negeri dan Sekolah Menengah Kejurusan Negeri Serta Pendidikan Khusus di Provinsi Riau - Rismahayani Rismahayani (Journal on Education, 2023)
In realizing equal distribution of education in accordance with the constitutional mandate of the 1945 Constitution and Law Number 20 of 2003 concerning the National Education System, the government has since 2017 implemented a "Zoning System" but in these regulations it has not been implemented properly specifically in effect and in accordance with the conditions of Riau Province p. Of course this really needs technical regulations in implementing zoning. The formulation of the problem in this research is a juridical study of the Governor of Riau Province Regulation Number 14 of 2021 concerning Acceptance of New Students at the State Senior High School and State Vocational High School Levels as well as Special Education in Riau Province. Research methods normative law. The conclusion in this study is that the existence of Governor Regulation Number 14 of 2021 will provide effectiveness in adapting population data, distance to schools, and school access from a number of areas whose validation is very accurate. So that it can provide convenience for the Riau Provincial Government in dividing the number of prospective students at the N.se Riau High School level